2008
DOI: 10.1038/nchembio.76
|View full text |Cite|
|
Sign up to set email alerts
|

NFκB selectivity of estrogen receptor ligands revealed by comparative crystallographic analyses

Abstract: Understanding how steroid hormones regulate physiological functions has been significantly advanced by structural biology approaches. However, progress has been hampered by significant misfolding of the ligand binding domains in heterologous expression systems and by conformational flexibility that interferes with crystallization. Here, we show that protein folding problems common to steroid hormone receptors are circumvented by a mutations that stabilize well-characterized conformations of the receptor. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
193
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(204 citation statements)
references
References 31 publications
(2 reference statements)
9
193
1
1
Order By: Relevance
“…S8 A and B). These data complement other comparisons that were made earlier with a nonsteroidal ligand (34,35). Additional characterization of the Y537S mutant via transient transfection of HeLa cells, Thermofluor and fluorescence anisotropy indicated that the mutation stabilizes the active conformation of the receptor without modifying the relative potencies of compounds (SI Appendix, Figs.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…S8 A and B). These data complement other comparisons that were made earlier with a nonsteroidal ligand (34,35). Additional characterization of the Y537S mutant via transient transfection of HeLa cells, Thermofluor and fluorescence anisotropy indicated that the mutation stabilizes the active conformation of the receptor without modifying the relative potencies of compounds (SI Appendix, Figs.…”
Section: Resultssupporting
confidence: 66%
“…4A). These suboptimal or complete lack of interactions induce a substantial reorientation of the H524 imidazole ring, which, as previously reported by Nettles et al (34), perturbs a key hydrogen bond network involving residues from loop L6-7, H3, and H11. Last but not least, we observed that, in the E 2 -bound structure, the 18-methyl group of E 2 is in contact with L525 and imposes a conformation that strengthens a network of van der Waals interactions involving T347, L525, and L536 (Fig.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…This is supported by the notion that the binding of HT to the AF-2 surface is of lower affinity compared with the cognate ligand-binding pocket (Wang et al 2006). Recently, it was reported that the Y537S ERa LBD mutation allows for the conformational stabilization during protein purification and subsequently allows for the addition of ligands to purified apoprotein (Nettles et al 2008). …”
Section: Structural Validation Of a Second Nr Ligand-binding Sitesupporting
confidence: 53%